Media Performance Analysis to Increase the Audio Quality in Multimedia Services - Sheela, D; Anil Kumar, KM (International Journal of Computer Sciences and Engineering, 2025)
Mobile communication has drastically increased in the software industry. Multimedia services in mobile communication has also increased its importance. Circuit Switched is now replaced by packet switched by most of the industries. These packets transmission is affected by the varied network parameters. The Audio is also transmitted in packets. The loss of packet or delay of the packet reduces the audio quality on the receiver side. To manage the packets and to maintain smooth audio quality various jitter buffer algorithms are implemented. The Performance of the jitter buffer algorithm affects the quality of audio. Our system analysis the jitter buffer management algorithm used on the receiver side to manage the packets arrived out of order, packet loss or duplicate packets received. The Media Performance Analysis System/tool checks the performance for varied network condition, different audio codecs and for different network profiles. It helps in easy analysis for the performance of the JBM .